Sex reassignment technology: the dilemma of transsexuals in Islam and Christianity - Ishak, Mohd. Shuhaimi; Haneef, Sayed Sikandar Shah (Springer, 2014)
The birth of people with confused or ambiguous sex makeup as a biological fact since the annals of history has posed the challenge of accommodating them within the binary gender of sociocultural systems. In this process, the role of religion as a defining factor in social engineering has been paramount. Major religions, such as Islam and Christianity, have addressed this issue within the frame of their God-ordained laws by devising a set of moral and legal imperatives specific to the ‘‘third gender.’’ Modern developments in medicine and biology, however, have made sex reassignment possible for this category of people, today called transsexuals. The question is: How do Islam and Christianity respond to it. After presenting an analytical view of both Muslim scholars and Christian religious authorities on the legitimacy of sex reassignment for transsexuals, this paper attempts to explore if such a dilemma can be resolved.